2013
DOI: 10.18433/j35c8b
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Modeling for Drug Dialyzability Prediction

Abstract: -Purpose. The purpose of this study was to develop an artificial neural network (ANN) model to predict drug removal during dialysis based on drug properties and dialysis conditions. Nine antihypertensive drugs were chosen as model for this study. Methods. Drugs were dissolved in a physiologic buffer and dialysed in vitro in different dialysis conditions (UFRmin/UFRmax, with/without BSA). Samples were taken at regular intervals and frozen at -20ºC until analysis. Extraction methods were developed for drugs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… Modified from Potpara et al 101 and Weir et al 102 Metoprolol elimination data from Hoffman et al 103 Labetalol protein binding data from Drugbank.ca 104 and dialyzability data from in vitro data by Daheb et al 105 All other dialyzability data from Frishman. 106 CKD, chronic kidney disease; CrCl, creatinine clearance; GFR, glomerular filtration rate.…”
Section: Rate Vs Rhythm Control Of Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“… Modified from Potpara et al 101 and Weir et al 102 Metoprolol elimination data from Hoffman et al 103 Labetalol protein binding data from Drugbank.ca 104 and dialyzability data from in vitro data by Daheb et al 105 All other dialyzability data from Frishman. 106 CKD, chronic kidney disease; CrCl, creatinine clearance; GFR, glomerular filtration rate.…”
Section: Rate Vs Rhythm Control Of Atrial Fibrillationmentioning
confidence: 99%
“… Labetalol protein binding data from Drugbank.ca 104 and dialyzability data from in vitro data by Daheb et al 105 …”
Section: Rate Vs Rhythm Control Of Atrial Fibrillationmentioning
confidence: 99%
“…In the final analysis, 76 studies were included for qualitative analysis, including 4 in vitro experiments [ 58 – 61 ], 2 animal experiments [ 62 , 63 ], 1 pharmacokinetic simulation study [ 64 ], 37 pharmacokinetic studies [ 65 101 ], and 32 case reports/series [ 13 , 15 , 35 , 102 – 130 ]. No comparative studies or randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The results were analyzed with the use of neural networks and a standard statistic method to calculate the impact of CsA on gene expression. The use of an artificial neural network has a wide range of usage in drug research, enabling the prediction of various processes [ 25 ]. In microarray analysis, the large amount of results can be used to create Kohonen self-organizing maps, which give the opportunity to cluster the analyzed gene expression data, showing possible interaction between them based on a mathematical algorithm [ 26 ].…”
Section: Discussionmentioning
confidence: 99%